A comparative behavioural study of mechanical hypersensitivity in 2 pain models in rats and humans - Reitz, Marie-Céline; Hrncic, Dragan; Treede, Rolf-Detlef; Caspani, Ombretta (Pain, 2016)
The assessment of pain sensitivity in humans has been standardized using quantitative sensory testing, whereas in animals mostlypaw withdrawal thresholds to diverse stimuli are measured. This study directly compares tests used in quantitative sensory testing(pinpricks, pressure algometer) with tests used in animal studies (electronic von Frey test: evF), which we applied to the dorsal hindlimbs of humans after high frequency stimulation and rats after tibial nerve transection. Both experimental models induce profoundmechanical hypersensitivity. At baseline, humans and rats showed a similar sensitivity to evF with 0.2 mm diameter tips, butsignificant differences for other test stimuli (allP,0.001). When expressed as force divided by circumference, baseline thresholdsfor 0.8 mm probes were higher than for 0.2 mm in both species (bothP,0.001) suggesting spatial summation. At similar probediameters, ramped stimuli showed higher baseline thresholds than stepped stimuli (P,0.01) but similar sensitivity to change. Forramped stimuli sensitivity to change was higher with small probe tips than large blunt tips in both pain models (P,0.01 in rat,P,0.05 in humans). These data show that rat paw withdrawal threshold to punctate stimuli (0.2 mm diameter) can be used as surrogateparameters for human mechanical pain sensitivity, but probe size and shape should be standardized. Hypersensitivity to bluntpressure - the leading positive sensory sign after peripheral nerve injury in humans - is a novel finding in the tibial nerve transectionmodel. By testing outside the primary zone of nerve damage (rat) or activation (humans), our methods likely involve effects of centralsensitization in both species.
Gesehen am 26.06.2019